Immersive Learning with Assemblr EDU: Advancing Reading Comprehension in EFL Classrooms through AR Technology - Mustakim Sagita; Zukhruf Farizi; Muhammad Khatami; Issy Yuliasri; Abdurrahman Faridi; Hendi Pratama (Sumber Belajar Sejahtera, 2025)
Despite the expanding application of Augmented Reality (AR) in educational settings, rigorous empirical investigations into its efficacy for enhancing reading comprehension among English as a Foreign Language (EFL) learners remain limited, particularly in the Indonesian higher education context. This study employed a quasi-experimental mixed-methods design to examine the impact of Assemblr EDU, an AR-based instructional application, on the reading comprehension performance of 104 undergraduate EFL learners at the B1 proficiency level. Utilizing the Dialang reading assessment and one-way analysis of covariance (ANCOVA), the quantitative findings revealed a statistically significant difference in posttest scores between the experimental group (M = 15.61) and the control group (M = 12.43), with a large effect size (partial η² = .919, p < .001), thereby affirming the pedagogical advantage of AR integration in reading instruction. Semi-structured interviews were conducted with six experienced EFL lecturers to contextualize the quantitative results further. Thematic analysis indicated that AR-supported instruction enhanced student motivation, vocabulary acquisition, and comprehension through multimodal interaction. However, technological constraints and limited access to digital resources were noted as implementation barriers. The study provides robust evidence supporting the efficacy of AR in improving EFL reading outcomes. It underscores the need for systemic support, including infrastructure readiness and targeted teacher training, to optimize its integration. These findings contribute to the theoretical and practical discourse on technology-enhanced language learning and offer implications for the design of future AR-based pedagogical interventions in EFL contexts.